Trust in Executive Search - the Client's Perspective - Rohrmeier, Juergen; Egan, Tom; Peisl, Thomas (Journal of Leadership, Accountability and Ethics, 2019)
A key aspect to successful headhunters is developing trust, yet how such trust is developed in the crucial initial exchange phase of a relationship with clients is an under-researched area. This study adopts a quantitative approach (survey of 175 clients) and the results show that perceived trustworthiness does have a significant impact on subsequent trust behaviour, with risk perception and trust propensity moderating this relationship. Such findings have important implications for headhunters (in terms of hiring and developing talent) and can assist clients to make better selection decisions.